1997
DOI: 10.1007/bf00941649
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Respiratory Distress and Cytokine Response after Cardiopulmonary Bypass

Abstract: The influence of cytokines on the inflammatory response in surgery has recently been the subject of investigations. We measured tumor necrotic factor-alpha (TNF-alpha), interleukin 1 beta (IL-1 beta), interleukin 6 (IL-6), interleukin 8 (IL-8), and granulocyte elastase (GEL) in 26 patients undergoing elective cardiac operations using cardiopulmonary bypass (CPB), preoperatively, immediately after CPB, and on post-operative days (PODs) 1, 3, and 6. To evaluate the effect of these cytokines on pulmonary function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…As for the systematic side effects attributed to the ECC, these have been extensively reported in literature (132)(133)(134)(135)(136)(137)(138)(139)(140). Immunologic disturbances induced by ECC, are considered to contribute to neoplastic disease spreading (101,141).…”
Section: Discussionmentioning
confidence: 99%
“…As for the systematic side effects attributed to the ECC, these have been extensively reported in literature (132)(133)(134)(135)(136)(137)(138)(139)(140). Immunologic disturbances induced by ECC, are considered to contribute to neoplastic disease spreading (101,141).…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-8 is another proinflammatory cytokine that can be correlated with impaired organ function after surgery. 29 In addition to proinflammatory cytokines, anti-inflammatory cytokines are also produced in response to stressful events such as surgery. 30 We measured IL-10 as a representative anti-inflammatory cytokine, but found no gender-specific cytokine production for IL-6, IL-8, or IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-8 (IL-8) has been proposed as a major chemotactic factor for the recruitment of neutrophils to extravascular sites of infl ammation. 6,7 Clinical studies have found rapidly increasing levels of circulating IL-8 in patients with large burns. 8 Moreover, the plasma concentration of IL-8 is correlated with the extent of burns and the presence of sepsis.…”
Section: Introductionmentioning
confidence: 99%